Moderating Effects of Internet Technology on How Pop-Up Ads and Brand Image Affect E-Commerce Competitiveness. - Virgo Simamora; Eka Sulastri Sitanggang Eka Sulastri Sitanggang (Al-Makki Publisher, 2023)
One important factor that makes a company or business successful in the market is its ability to create competitiveness against its competitors using internet technology. This study aims to explore the moderating role of internet technology on the influence of pop-up advertisements and brand image on a company's competitiveness. The primary data collection method used in this study is a survey, which involves 100 respondents who have a permanent job, are e-commerce users, and residing in DKI Jakarta. The collected data was obtained through a validated and reliable questionnaire. The results of this study indicate that pop-up ads and brand image have a significant and positive impact on e-commerce competitiveness. Additionally, internet technology also has a significant and positive impact on competitiveness. Furthermore, the moderation effect of internet technology is positively associated with the influence of pop-up advertisements on competitiveness and also positively moderates the impact of brand image on competitiveness.